Pentingnya Penanaman Karakter Pada Anak Sekolah Dasar Sdn Banyuajuh 3 - Elly Dwi Fauzianah; Natasya Regina; Dela Nur Fitriani (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
Education is crucial, primarily for the improvement of morality and character formation. Character refers to the attitudes or traits present in every individual. The aim of this research is to understand the various characters exhibited by students at SDN Banyuajuh 3 and to describe how character development is implemented among these students. The research employs a qualitative research method, and the results of this study include:1) Character cultivation among students is carried out through the application of core values such as cooperation, discipline, responsibility, honesty, creativity, and religious values.2) Character development in students is achieved through habitual practices and real-life applications.3) Teachers employ various strategies to instill character in students, including reminders, invitations, reprimands, and setting a good example.4) Challenges in character development at SDN Banyuajuh 3 include environmental factors and family-related factors or parental influences